Detection and genetic polymorphism of human herpes virus type 8 in endemic or epidemic Kaposi's sarcoma from West and Central Africa, and South America - (:unkn) unknown (My University, 2000)
Kaposi's-sarcoma-associated herpesvirus(KSHV)/human-herpes-virus-8(HHV-8) sequences originally detected in AIDS-associated Kaposi's sarcoma have been found in almost every KS tested, whether endemic, classic, iatrogenic or epidemic. Most of the studies on African KS involved East African patients. We report herewith the study of 17 African or Guyanan KS patients, 3 with epidemic KS (EKS) from Central African Republic, 3 from Senegal (2 EKS and 1 endemic KS), 3 EKS from Cameroon and 8 from French Guiana (3 EKS and 5 endemic KS). Serum-specific antibodies directed against latent and/or lytic HHV-8 antigens were present in 16 of them (94%), detected either by immunofluorescence assay and/or by immunoperoxidase. Polymerase chain reaction (PCR), using specific primers for HHV-8 ORF26 (233 bp) and ORF75 (601 bp), was carried out on DNA extracted from KS cutaneous biopsies, clinically uninvolved skin biopsies and peripheral-blood mononuclear cells (PBMC). HHV-8 DNA was detected in 16 out of 16 (100%) KS biopsies, regardless of their origin or clinico-pathological sub-type, in 7 out of 15 (47%) normal skin samples and 7 out of 16 (44%) PBMC. Comparative PCR, carried out in 7 patients, regularly found a much higher viral load in KS biopsies than in autologous normal skin and PBMC samples. Sequencing of fragments of the ORF26 and of the ORF75 demonstrated that the 16 HHV-8 strains were of the A, B or C sub-type. Furthermore, sequences of the entire ORF K1 of 4 strains showed that these HHV-8 strains of African origin were of the A5 or the B sub-type.
Keywords: African Research